Pre-RA: Can early diagnosis lead to prevention?. Issue 1 (March 2022) - Haville, Salina; Deane, Kevin D.
Abstract: Rheumatoid arthritis (RA) is currently diagnosed and treated once an individual displays the clinical findings of inflammatory arthritis (IA). However, growing evidence supports that there is a 'pre-RA' stage that can be identified through factors such as autoantibodies in absence of clinically apparent IA. In particular, biomarkers, including antibodies to citrullinated protein antigens (ACPA), demonstrate a high risk for future IA/RA, and multiple clinical trials have been developed to intervene in individuals in pre-RA to prevent or delay clinically apparent disease. Herein, we will discuss in more depth what is currently known about the natural history of RA, and the emerging possibility that early 'diagnosis' of RA-related autoimmunity followed by an intervention can lead to the delay or prevention of the first onset of clinically apparent RA.